New techniques for computer-based simulation in surgical training. (25th April 2011) - Turini, Giuseppe; Pietroni, Nico; Megali, Giuseppe; Ganovelli, Fabio; Pietrabissa, Andrea; Mosca, Franco
Scientific community in medicine indicates the disruptive potential of the application of Virtual Reality (VR) to the training in the medical field. This paper presents some research and applicative results on Computer Assisted Surgery (CAS) achieved in the framework of EndoCAS, a Center of Excellence in Pisa. The research has involved: segmentation algorithms for volumetric datasets, bone drilling simulation, simulation and virtual cutting of human tissue, simulation of rope dynamics to reproduce a suture procedure in MIS. Our purpose is to enhance the surgical training with new techniques to carry the surgical training to a next level of realism.